Rice is life : (International Rice Commission, 2005)
The first part of this book presents the International Year of Rice and hundreds of events that took place worldwide in 2004 to implement the year with the participation of people from rural and urban areas, developed and developing countries, and of governments and non-governmental organizations. The second part of the book offer an opportunity to expand the understanding of the importance of rice in our planet by describing the Facets of Rice is Life - rice production and hunger reduction; rice and human nutrition; rice as a symbol of cultural identity and global unity; rice and environment; rice and agricultural biodiversity; and labor, gender and livelihood in rice. The last part of the book focuses on the importance of rice and, indeed, of agriculture, in and beyond the new millennium.